Analisis Efisiensi Pasar Modal di Indonesia - Liani, Tiara; br. Simbolon, Lasmia Rotua; Anwar, Halisya Rahmawati; br. Naibaho, Ester Agustina Indah (CV. Kalimasada Group, 2024)
This research aims to determine the efficiency of the capital market in Indonesia. This research uses a descriptive method. This research uses secondary data from the Financial Services Authority (OJK) and the Indonesian Stock Exchange (BEI) in the Financial Reports section. The research approach used is quantitative. This research uses a population containing all closing stock prices of consumer goods listed on the Indonesia Stock Exchange, totaling 52 companies. The sample in this research is consumer goods industry companies listed daily on the Indonesian Stock Exchange. This research uses a sampling technique, namely the purposive sampling technique. Based on research analysis using the normality test, the t-test for the difference between two sample means is related (paired sample t-test). The analysis results show that lag return (r-1), lag return (r-2), and trading volume are not proven to affect stock performance positively. Thus, the efficient market hypothesis applies